Violencia no conyugal contra la mujer en la familia. Medellín, 1996 (1998)
ABSTRACT: In the present article, the author presents an analytical and empirical research on the prevalence physical and psychological non-conjugal violence against Colombian women in the city of Medellin, taking into consideration sociodemographic variables. A random sample of 461 women older than 12 were proportionally selected from the socio-economic strata 1, 2 and 3. Furthermore , violence as a punishment strategy, its background, women´s perception and response of violence , and women´s perception of power were analyzed. The following results were drawn: 1) 57.2% of women have been once beaten at home and 43.0% have been beaten in the last year. 2) Of the latter, only 39.3% really felt mistreated, being their mother the person who most beats them. 3) Mistreatment is proportional to the socio-economic level; the lower the socio-economic level, the more women are mistreated. 4) Half of women believe that physical punishment is necessary in disciplining their children. 5) 39.2% of women older than 20 and 30.8% of women younger than more felt being mistreated during their childhood.